Evaluation of an Intervention Program to Foster Self-Regulated Learning and Academic Achievement in Latin Instruction. (27th November 2012) - Wagner, Daniela; Perels, Franziska
Abstract : The study's aim was to develop two different intervention programs and to evaluate their contribution to students' self-regulated learning and academic achievement in Latin classes. The concept of our study referred to a process-focused model of self-regulated learning that divides the phases of the self-regulated learning process into different areas, which we applied to domain-specific translation strategies. Within a pre-, post-, and follow-up-test design with 109 tenth graders, self-regulated learning skills and translation competency as well as translation strategy application were assessed using both a self-regulation questionnaire and a standardized translation test. Three different conditions were compared: (a) combined training group (ComG): self-regulated learning and translation, (b) translation training only (TG), and (c) control group (CG). The intervention consisted of nine sessions spread over a period of three weeks. Results of analyses of variance with time as a repeated measurement indicated interaction effects between time and groups for self-regulated learning in favor of the intervention groups. The ComG showed marginally higher self-regulatory skills than the TG. Regarding the translation competencies as well as the strategy application, the results revealed significant training effects in comparison to the control group, with the TG showing the highest increase.